The US policy towards European integration: teh case of Turkey’s accession to the EU - İşeri, Emre (My University, 2005)
Most academic studies on the process of European integration do not pay much attention to the international system and its requirements. The process of European integration is usually analyzed as being a consequence of internal dynamics. However, European integration is not solely dependent on internal dynamics. The external dynamics should also be emphasized as independent variables. This thesis aims to look at the picture from the perspective of the sole hegemonic power, the United States (US), and analyze Turkey’s accession to the EU from that perspective. Washington conceives the continent of Europe as a springboard to Eurasia, center of the world according to many geo-politics theories. Moreover, Washington considered European enlargement, a means of wide spreading western values of democracy and liberalism to these regions. Washington’s relationship with Turkey has always been founded on strategic considerations. Turkey is a pivotal state in the region. Moreover, Turkey has had western orientation since the early days of its foundation. It has been endeavoring to become a member of the European club. Thus, Turkey has the potential to inspire its neighboring regions and influence them to orient toward western institutions and values. In sum, anchoring Turkey to western institutions is the main reason for Washington’s support for Turkey’s accession to the EU. Washington’s view of the EU enlargement as a duty of Europeans in order to share their burdens in transatlantic cooperation overlaps with the Washington’s vision of Turkey’s accession to the EU.
Keywords: Avrupa Birliği_Dış İlişkiler_Türkiye; Siyasal bilimler (Siyaset bilimi); Toplum bilimleri; Türkiye_Dış İlişkiler_Avrupa Birliği